(untitled) (Eurasian Journal of Engineering and Technology, 2023)
According to the results of the research conducted in this article, the introduction of complex chemical additives into the composition of expanded clay concrete mixtures significantly changes their properties. Complex chemical additives increase the properties of expanded clay concrete mixture, improve the properties of workability, reduce water demand.